A Review on Expired Drug-Based Corrosion Inhibitors: Chemical Composition, Structural Effects, Inhibition Mechanism, Current Challenges, and Future Prospects - Muhamad Jalil Baari; Carla Wulandari Sabandar (Indonesian Journal of Chemistry, 2021)
This comprehensive review highlighted how the expired drugs manage corrosion reactions on metal/alloy surfaces, especially types of carbon/mild steel, Sabic iron, copper, and aluminium in NaCl or acid solution. Several types of expired drugs and the optimum conditions presented in this review were summarized from relevant studies. The performance of expired drugs which covers inhibition efficiency, inhibition mechanisms, and metal surface analysis was informed. The contribution of the chemical composition, molecular structure, compatible treatment conditions, and some corrosion analysis methods were mentioned. Current challenges and future prospects were also discussed for further investigations and developments to obtain superior inhibitors and save the environment.